Mechanistic insight into bacterial entrapment by septin cage reconstitution - Damián Lobato-Márquez (Nature Portfolio, 2021)
Septins are cytoskeletal proteins that assemble into complexes and contribute to immunity by entrapping intracellular bacteria in cage-like structures. Here, Lobato-Márquez et al. reconstitute septin cages in vitro using purified recombinant complexes, and study how these recognize bacterial cells and assemble as filaments on their surface.